Combination of CNN and SMOTE-IPF for Early Detection of Diabetes Patients in Thermogram Images - W Mega Adhi Agam Pradhana; Gede Angga Pradipta; Roy Rudolf Huizen (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2025)
This study aims to enhance the early detection of diabetic complications through the analysis of plantar foot thermogram images using deep learning techniques. A total of 334 thermographic images were utilized, comprising 244 images from 122 diabetic patients (DM class) and 90 images from 45 non-diabetic individuals (control group, CG class). To address the dataset’s imbalance (ratio of 2.64), the Synthetic Minority Over-sampling Technique with Iterative-Partitioning Filter (SMOTE-IPF) was applied both before and after feature extraction. Image quality was further enhanced using Adaptive Histogram Equalization (AHE) and Gamma Correction preprocessing techniques. A Convolutional Neural Network (CNN) model was trained and evaluated on an independent test set of 54 images. The model achieved outstanding results: 99.37% accuracy, 99.37% precision, 100% recall, and a 99.68% F1-score for AHE-processed images. Gamma-corrected images achieved 98.50% accuracy, while original images reached 97.20%. These findings demonstrate the combined value of data balancing and preprocessing in improving non-invasive diabetic foot ulcer detection, offering a promising diagnostic aid for clinical settings.